Efficacy of Salak Seed and Pomelo Peel Extracts on HeLa Cell Apoptosis and Proliferation - Azis, Aditya Latiful; Ceria, Asy Syifa Paras; Tsany, Shabrina Farras; Saffana, Rahmalia Diani; Nuryanto, Faqih Fikri; Tunjung, Woro Anindito Sri (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
The development of adjuvant therapies is vital for reducing cancer recurrence and minimizing the adverse effects of conventional treatments. Salak seeds (Salacca zalacca) and pomelo peels (Citrus maxima) are rich in bioactive compounds such as terpenoids, flavonoids, lycopene, and polyphenols, making them promising candidates for adjuvant cancer therapy. This study evaluated the anticancer effects of their individual and combined extracts. Bioactive compounds in salak seed (S) and pomelo peel (J) extracts were identified using gas chromatography-mass spectrometry (GC-MS) and analyzed in silico to assess their binding affinities to key target proteins: COX-2 (anti-inflammatory), caspase-3 (apoptosis induction), and PI3K (cell proliferation). The extracts were tested in vitro on cervical cancer HeLa cells at varying treatment groups: S; J; 1S3J; 1S1J; and 3S1J. Assays evaluated anti-inflammatory activity, cytotoxicity, cell migration inhibition, and apoptosis induction. Both in silico and in vitro analyses consistently demonstrated that the extracts significantly reduced cell viability exhibited anti-inflammatory effects, inhibited cell proliferation, and enhanced apoptosis. Among the tested treatments, the 1S1J combination showed the most pronounced effects across all parameters, highlighting its synergistic interaction, and superior therapeutic potential. These findings position the 1S1J combination as an optimal candidate for adjuvant cervical cancer therapy, warranting further investigation.